The Year-End LIFO Inventory Purchasing Decision: An Empirical Test - Frankel, Micah; Trezevant, Robert (The Accounting Review, 1994)
[Several analytical models of the year-end inventory purchasing decision of a LIFO firm have been developed (Cohen and Halperin 1980; Halperin 1979, 1981; Biddle and Martin 1985).1 This study finds empirical support for the prediction of these models that, since only LIFO firms reduce their tax burden by purchasing additional inventory (i.e., "extra" inventory) at year-end, LIFO firms are more likely to purchase extra inventory at year-end than FIFO firms. This research also provides evidence that high-tax LIFO firms are more likely to purchase extra inventory at year-end than low-tax LIFO firms. This behavior is predicted because a LIFO firm's tax savings from purchasing extra inventory at year-end are increasing in its marginal tax rate. Additional evidence of tax-motivated year-end inventory purchases is offered by tests which find that (1) consistently high-tax LIFO firms accelerated their year-end inventory acquisitions-and thus reduced their taxable income-to a significant degree in the years immediately preceding the reduction in tax rates mandated by the Tax Reform Act of 1986; and (2) differences in tax status are not related to differences in fourth quarter inventory purchasing behavior for FIFO firms. The results of this study indicate that taxes have a sizable effect on the inventory purchasing policy of LIFO firms. For example, (1) the estimated difference in the percentage of annual inventory purchases made in the fourth quarter between high-tax and low-tax LIFO firms is equivalent, on average, to 12.66 million of purchases (3.8 percent of ending inventory); and (2) the estimated decrease in inventory purchases made in the fourth quarter by LIFO firms that move from a high-tax status in one year to a low-tax status in the following year is equivalent, on average, to 28.89 million of purchases (12.1 percent of ending inventory). These large dollar amounts lend credence to the concern that year-end LIFO inventory purchases made for tax purposes may lead to inventory management inefficiencies (Jannis et al. 1980, 186).]